Concise Synthesis of N-Aryl Tetrahydroquinolines via a One-Pot Sequential Reduction of Quinoline/Chan–Evans–Lam Coupling Reaction - Bhattacharyya, Dipanjan; Senapati, Siddhartha Kumar; Das, Animesh (Synlett, 2022)
A boronic acid catalyzed one-pot reduction of quinolines with Hantzsch ester followed by N-arylation via external base-free Chan–Evans–Lam coupling has been demonstrated. This step-economical synthesis of N-aryl tetrahydroquinolines has been accomplished from readily available quinoline, Hantzsch ester, and arylboronic acid under mild reaction conditions. The dual role of boronic acid as a catalyst (in the reduction of quinolines) and a reagent (in the N-arylation) has been realized for the first time. The use of an inexpensive N-arylation protocol, aerobic reaction conditions, and functional group diversity are important practical features.
Keywords: N-aryl tetrahydroquinolines; dual role boronic acid; Chan–Evans–Lam coupling; N-arylation; one-pot reaction